IMPLEMENTASI STRATEGI MANAJEMEN RETAIL SETELAH PANDEMI DI LOTTE MART CENTRE POINT - Lambok Manurung; Ningsi, Etty Harya (LPPM Institut Pendidikan Nusantara Global, 2024)
The COVID-19 pandemic has had a significant impact on the economy and consumer behavior in Indonesia. In the midst of this situation, Lotte Mart Centre Point, as a retail store, faces a major challenge to survive and adapt to the changes. To address this challenge, a community service team from Universitas Battuta has implemented a retail management strategy using the Marketing Mix approach (Product, Price, Place, Promotion, people, process, physical evidence). This research aims to provide training, mentoring, and guidance to Lotte Mart Centre Point partners in implementing effective marketing strategies. Through training and mentoring activities, there has been a significant improvement in the enthusiasm and communication skills of partner employees. Evaluation shows that understanding and implementation of the Marketing Mix marketing strategy have also shown positive improvements. It is hoped that the results of this community service activity will help improve the economic performance of partners and strengthen their position amidst increasingly competitive markets. The conclusion of this study is that understanding and implementing the Marketing Mix marketing strategy is key to success in addressing economic challenges and changes in consumer behavior.